2008
DOI: 10.1007/s00264-008-0564-5
|View full text |Cite
|
Sign up to set email alerts
|

Mini-invasive surgical repair of the Achilles tendon—does it reduce post-operative morbidity?

Abstract: The surgical benefit of minimally invasive tendo Achilles repair (n=25) with early weight-bearing mobilisation after rupture of the tendo Achilles was compared with operative treatment using an open technique (n=34) with full weight-bearing after 8 weeks of surgical repair. The minimally invasive technique provided no evidence of wound problems and a functional benefit from early weightbearing mobilisation. However, we noted that increased postoperative morbidity in terms of wound infection (n=7) leading to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
50
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 8 publications
(11 reference statements)
3
50
0
Order By: Relevance
“…There was no difference in the number of reruptures compared with open repair 70 . Mini-open repair also had significantly fewer severe wound infections and superficial infections than open repair, as well as fewer minor surgical site infections 69 .…”
Section: Treatment Of An Acute Rupturementioning
confidence: 97%
See 1 more Smart Citation
“…There was no difference in the number of reruptures compared with open repair 70 . Mini-open repair also had significantly fewer severe wound infections and superficial infections than open repair, as well as fewer minor surgical site infections 69 .…”
Section: Treatment Of An Acute Rupturementioning
confidence: 97%
“…This approach involves small incisions that allow direct visualization of the ruptured tendon ends. Studies have found that patients who underwent mini-open repair returned to walking, stair climbing, and sports in significantly less time compared with those undergoing standard open repair 69,70 . There was no difference in the number of reruptures compared with open repair 70 .…”
Section: Treatment Of An Acute Rupturementioning
confidence: 98%
“…Some studies have advocated a plantigrade or neutral position with restricted dorsiflexion, while others are in favour of keeping the ankle in maximum plantar flexion to reduce the strain on the TA repair site. (34)(35)(36) The American Academy of Orthopaedic Surgeons published its first clinical guidelines on the treatment of TA rupture in 2010. (37) The authors recognised that despite the range of protocols and 'protective devices' available, there was a lack of clinical consensus regarding which devices should be used, the degree of ankle plantar flexion these devices should facilitate and how long these devices should be worn.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is disagreement about the degrees of plantar lexion that should be maintained within the orthoses. Some studies have advocated that the ankle should be positioned in neutral (plantar-grade) but with restricted dorsi lexion, while others have used three heel-wedge inserts such that the ankle joint is initially maintained at near full plantar lexion [101]. Finally, it is important to decide when weight-bearing should be permitted (day one or within 2 weeks), how long the orthoses should be worn and whether or not to allow active range of movement exercises throughout the period when the orthosis is worn [29,102,103].…”
Section: Discussionmentioning
confidence: 99%